Short Marketing Circuits (CCC): An approach from agro-ecological experiences in Brazilian territory - Buenaventura, Ivonne; da Paixão Sousa, Romier; Gómez López, José Daniel (Cooperativismo & Desarrollo, 2021)
This article discusses the forms of commercialization of agro-food products based on agro-ecological families of farmers, through short circuits; based on the social construction of markets as a political act by producers and consumers. For this analysis, a bibliographic review was made addressing theoretical aspects of the social construction of the markets and experiences in the Brazilian territory referring to short marketing circuits. The results show that all these experiences, from their particularities and different strategies implemented, have done an important job in the promotion of fair trade and the solidarity economy. However, the processes of social construction of markets are highlighted, involving organized farming families and responsible consumption groups, which have demonstrated how the proximity, knowledge and trust relationships between production and consumption facilitate the marketing processes through circuits commercialization short, in relation to other channels such as the institutional market and government programs, which are made up of different bureaucratic procedures, which obviously hinder the commercialization of family farming products.
Keywords: short marketing circuits; social market construction; cooperatives and associativism; fair trade